Finding Gobi : a little dog with a very big heart - Leonard, Dion; Borlase, Craig (Nashville, Tennessee : W Publishing Group, an imprint of Thomas Nelson, 2017)
While racing through the Gobi Desert in China and Mongolia, the author, a seasoned ultramarathoner, encounters a stray dog who, keeping pace with him for nearly 80 miles, gives him a new perspective on life, causing him to fight to bring her home with him with the help of strangers and a viral outpouring of assistance on the internet.
Leonard, a seasoned ultramarathoner, encountered a stray dog while he was racing through the Gobi Desert in China and Mongolia. The dog kept pace with him for nearly 80 miles. Taking care of the dog gave Leonard a new perspective on life. He named the dog Gobi, and fought to bring her home with him with the help of strangers and a viral outpouring of assistance on the internet.
Keywords: Leonard, Dion; Gobi -- (Dog); Dog owners -- Scotland -- Edinburgh -- Biography; Male long-distance runners -- Scotland -- Edinburgh -- Biography; Dogs -- Gobi Desert (Mongolia and China) -- Biography; Ultra running -- Gobi Desert (Mongolia and China); Human-animal relationships; Dog adoption; BIOGRAPHY & AUTOBIOGRAPHY / Sports; Autobiographies